2021
DOI: 10.33024/hjk.v15i3.5407
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan dan sikap dengan kepatuhan protokol kesehatan 5 M di masa Pandemi Covid-19

Abstract: The knowledge, attitude, and compliance: Implementation of health protocol policy in Covid-19 prevention Background: The World Health Organization as Public Health Emergency of International Concern, PHEIC) has designated coronavirus Disease–19. The ways to transmit Covid-19 is through hand contact and hand hygiene, the most effective way to prevent nosocomial infections by attitude and knowledge of nurses play an important role in implementing the implementation of hand hygiene in a health facility environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…Additionally, the study reported a significant difference in the attitude of high school students before and after triggering in controlling Covid-19, demonstrating a pvalue = 0.000. This finding aligns with Gunawan et al [22] , which establishes a significant correlation between attitudes and compliance with the 5 M health protocol during the Covid-19 pandemic. Triggering strategies involving fear and disgust induction, such as using a spray assumed to contain pathogenic microbes, create awareness about the risks of contracting respiratory diseases like Covid-19, leading to improved attitudes among students towards controlling the spread of the virus.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the study reported a significant difference in the attitude of high school students before and after triggering in controlling Covid-19, demonstrating a pvalue = 0.000. This finding aligns with Gunawan et al [22] , which establishes a significant correlation between attitudes and compliance with the 5 M health protocol during the Covid-19 pandemic. Triggering strategies involving fear and disgust induction, such as using a spray assumed to contain pathogenic microbes, create awareness about the risks of contracting respiratory diseases like Covid-19, leading to improved attitudes among students towards controlling the spread of the virus.…”
Section: Discussionsupporting
confidence: 91%
“…Serta dibutuhkan peningkatan pengetahuan pedagang terhadap perilaku hidup bersih dan sehat dalam upaya pencegahan penularan Covid-19 (Hasma et al, 2021) Pada penelitian ini juga ditemukan hubungan sikap dengan kepatuhan pedagang dalam menerapkan protokol kesehatan pencegahan Covid-19. Hasil penelitian sejalan dengan (Gunawan et al, 2021) yang mendapatkan ada hubungan yang bermakna antara sikap dengan kepatuhan pelaksanaan protokol kesehatan (p-value=0,000) Di dukung penelitian (Safitri, 2019) yang menemukan hubungan signifikan sikap dengan perilaku pencegahan 004) dan penelitian (Tetartor et al, 2021) yang melaporan ada hubungan signfikan sikap dengan kepatuhan pelaksanaan protokol kesehatan pencegahan 000). Sikap adalah salah satu respons tertutup seseorang terhadap stimulus atau objek tertentu.…”
Section: Hasil Dan Pembahasanunclassified
“…5,6,7,8 Penelitian ini dilakukan di SMA Angkasa Kabupaten Maros. Populasi dalam penelitian adalah siswa di SMA Angkasa Kabupaten Maros.…”
unclassified